Legislation Development in Vietnam: Is the criminal law becoming more humane? - Trinh, Duc Hieu (Edelweiss Applied Science and Technology, 2024)
After four decades since the present of the first “modern” Criminal code of Vietnam in 1985, Vietnamese lawmakers have reached many remarkable milestones in terms of criminal justice policy and legislation. The paper shall discuss and clarify 02 main hypotheses. Firstly, there are 05 criteria to evaluate the clemency of the Vietnamese criminal law, including: 1) The proportion between the number of very serious, extremely serious crimes and total number of crimes; 2) Severity of the punishments in the 2015 Criminal Code; 3) The number of provisions on exemption from serving sentences, reduction of sentence duration and conviction expungement; 4) The number of provisions on penalty decisions in favor of the offenders; 5) The proportion between the decriminalized crimes and criminalized conducts in the criminal code. Secondly, based on analyzing these criteria, the paper shall prove that Vietnamese criminal law is becoming more humane. The achieved developments come from several reasons. The main one is that the entire political regime of Vietnam, with the key role of Communist Party, participated in the reformation process of the criminal law.